CCL3L1 gene-containing segmental duplications and polymorphisms in CCR5 affect risk of systemic lupus erythaematosus. Issue 8 (30th October 2007) - Mamtani, M; Rovin, B; Brey, R; Camargo, J F; Kulkarni, H; Herrera, M; Correa, P; Holliday, S; Anaya, J-M; Ahuja, S K
Abstract : Objectives: There is an enrichment of immune response genes that are subject to copy number variations (CNVs). However, there is limited understanding of their impact on susceptibility to human diseases. CC chemokine ligand 3 like-1 (CCL3L1) is a potent ligand for the HIV coreceptor, CC chemokine receptor 5 (CCR5), and we have demonstrated previously an association between CCL3L1 -gene containing segmental duplications and polymorphisms in CCR5 and HIV/AIDS susceptibility. Here, we determined the association between these genetic variations and risk of developing systemic lupus erythaematosus (SLE), differential recruitment of CD3+ and CD68+ leukocytes to the kidney, clinical severity of SLE reflected by autoantibody titres and the risk of renal complications in SLE. Methods: We genotyped 1084 subjects (469 cases of SLE and 615 matched controls with no autoimmune disease) from three geographically distinct cohorts for variations in CCL3L1 and CCR5 . Results: Deviation from the average copy number of CCL3L1 found in European populations increased the risk of SLE and modified the SLE-influencing effects of CCR5 haplotypes. The CCR5 human haplogroup (HH)E and CCR5-Δ32 -bearing HHG*2 haplotypes were associated with an increased risk of developing SLE. An individual's CCL3L1–CCR5 genotype strongly predicted the overall risk of SLE, high autoantibody titres, and lupus nephritis as well as the differential recruitment of leukocytes in subjects with lupus nephritis. The CCR5 HHE/HHG*2 genotype was associated with the maximal risk of developing SLE. Conclusion: CCR5 haplotypes HHE and HHG*2 strongly influence the risk of SLE. The copy number of CCL3L1 influences risk of SLE and modifies the SLE-influencing effects associated with CCR5 genotypes. These findings implicate a key role of the CCL3L1–CCR5 axis in the pathogenesis of SLE.